SURVEY : CRYPTOGRAPHY OPTIMIZATION ALGORITHMS - M Geetha; K Akila (IJISCS (International Journal of Information System and Computer Science), 2018)
With the advent of e-commerce, it has become extremely essential to tackle the sensitive issues of affording data security, especially in the ever-blooming open network environment of the modern era. The encrypting technologies of the time-honored cryptography are generally employed to shelter data safety extensively. The term ‘cryptography’ refers to the process of safeguarding the secret data against access by unscrupulous persons in scenarios where it is humanly impossible to furnish physical protection. It deals with the methods which convert the data between intelligible and unintelligible forms by encryption/decryption functions with the management of key(s). Nowadays cryptographic key management issues that arise due to the distributed nature of IT resources, as well the distributed nature of their control. Recently these issues are solved by optimization algorithms utilized in the cryptographic algorithms. The purpose of this paper is to give a survey of optimal cryptographic keys that can be developed with the help of optimization algorithms, and to address their merits to the real-worldscenarios.AbstractWith the advent of e-commerce, it has become extremely essential to tackle the sensitive issues of affording data security, especially in the ever-blooming open network environment of the modern era. The encrypting technologies of the time-honored cryptography are generally employed to shelter data safety extensively. The term ‘cryptography’ refers to the process of safeguarding the secret data against access by unscrupulous persons in scenarios where it is humanly impossible to furnish physical protection. It deals with the methods which convert the data between intelligible and unintelligible forms by encryption/decryption functions with the management of key(s). Nowadays cryptographic key management issues that arise due to the distributed nature of IT resources, as well the distributed nature of their control. Recently these issues are solved by optimization algorithms utilized in the cryptographic algorithms. The purpose of this paper is to give a survey of optimal cryptographic keys that can be developed with the help of optimization algorithms, and to address their merits to the real-worldscenarios. Keywords:Cryptography; Encryption; Decryption; Key Management; Optimization algorithm;